2006
DOI: 10.3346/jkms.2006.21.5.871
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Cyclooxygenase-2, p53 and Ki-67 in Gastric Cancer

Abstract: It has been reported that p53 mutation may contribute to upregulate cyclooxygenase (COX)-2 expression that is observed in malignant tissues. These molecules are involved in carcinogenesis by affecting tumor cell proliferation. The aim of this study was to examine the relationship between COX-2 or p53 expression and clinico-pathological characteristics including tumor cell proliferation in gastric cancer. COX-2 and p53 expressions were investigated with immunostaining, in tissue specimens obtained from 119 pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
23
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 31 publications
8
23
0
Order By: Relevance
“…Several studies [4][5][6][7] have shown that the cyclooxygenase-2 (COX-2) gene is overexpressed in gastric cancer, suggesting a possible role of COX-2 in gastric carcinogenesis. COX-2 participates in several important cellular activities, for example cell proliferation, apoptosis, and angiogenesis [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies [4][5][6][7] have shown that the cyclooxygenase-2 (COX-2) gene is overexpressed in gastric cancer, suggesting a possible role of COX-2 in gastric carcinogenesis. COX-2 participates in several important cellular activities, for example cell proliferation, apoptosis, and angiogenesis [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…The included data were extracted from each of the eligible studies (7,9,10,(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31): the first author's name, year of publication, study location, antibody manufacturer, dilution ratio of Ki-67 or MIB-1 antibody, cutoff value for high Ki-67 LI, number of patients analyzed, and pathological tumor-node-metastasis (pTNM) stage. For quantitative aggregation of survival results, the correlation between high Ki-67 LI and overall or disease-free survival rate was analyzed according to the hazard ratio (HR) using 1 of 3 methods.…”
Section: Data Extractionmentioning
confidence: 99%
“…Y. Joo et al (2006) [12] reported, that there is a direct correlation between Ki-67 and p53 expression levels in the tumor cells of gastric cancer.…”
Section: Resultsmentioning
confidence: 99%
“…2). It is known, that in 60 % of highly differentiated gastric cancer, including intestinal-type gastric adenocarcinoma, TP53-mutations are identifi ed [12,14]. TP53-gene encodes the synthesis of p53, which is detected by the corresponding immunohistochemical reaction [13].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation